ELECTRIC VEHICLE SAFETY: AN INNOVATIVE AND CRITICAL ANALYSIS OF FIRE RISKS AND MITIGATION STRATEGIES - Caracas, Ana Katherine Silveira Pereira; Winter, Eduardo; Nobre, Joel de Abreu; Gomes, Rickardo Léo Ramos; Caracas Neto, Roberto Augusto; Carvalho, Tecia Vieira; Duch, Thiago Costa (Seven Editora, 2026)
The growing adoption of electric vehicles (EVS) represents a significant transformation in sustainable urban mobility. however, fire safety, particularly with regard to lithium-ion batteries, has emerged as a relevant challenge. This study adopts a qualitative and exploratory approach, with analytical and documentary emphasis, grounded in the innovative and pioneering nature of the research within the brazilian context. The main objective of this article is to propose a critical analysis of global trends in electric vehicle safety, with particular emphasis on fire suppression and related innovations aimed at enhancing safety for users, owners, and residential condominiums. furthermore, the study highlights the need for international harmonization and for the development of specialized training for fire response professionals. The research is innovative and pioneering in consolidating dispersed data and proposing an integrated and strategic approach to the prevention and suppression of fires in EVS. The results underscore the need for specific regulations, specialized training, and technological innovations to ensure safe and effective electric mobility. The study encompasses international data, emerging regulations, and technological innovations, offering a current and forward-looking overview of EV safety.